2020
DOI: 10.3390/biomedicines8120573
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Blue Light Interaction with Human Keloid-Derived Fibroblasts

Abstract: Keloids are an exuberant response to wound healing, characterized by an exaggerated synthesis of collagen, probably due to the increase of fibroblasts activity and to the reduction of their apoptosis rate: currently no standard treatments or pharmacological therapies are able to prevent keloid recurrence. To reach this goal, in recent years some physical treatments have been proposed, and among them the PhotoBioModulation therapy (PBM). This work analyses the effects of a blue LED light irradiation (410–430 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 63 publications
3
20
0
Order By: Relevance
“…These cells stimulated (i) an early inflammatory response; (ii) angiogenesis, thanks to the secretion of TNF-α [ 36 ]; and (iii) the response of fibroblasts that switched into myofibroblasts, which played a role in wound closure, evidenced by re-epithelialization and collagen deposition [ 36 , 37 , 38 , 39 , 40 , 41 ]. Therefore, together with our previous investigation [ 15 , 16 , 19 , 41 , 42 , 43 ], these results show that blue-LED-light irradiation induces a quicker healing process.…”
Section: Discussionsupporting
confidence: 85%
“…These cells stimulated (i) an early inflammatory response; (ii) angiogenesis, thanks to the secretion of TNF-α [ 36 ]; and (iii) the response of fibroblasts that switched into myofibroblasts, which played a role in wound closure, evidenced by re-epithelialization and collagen deposition [ 36 , 37 , 38 , 39 , 40 , 41 ]. Therefore, together with our previous investigation [ 15 , 16 , 19 , 41 , 42 , 43 ], these results show that blue-LED-light irradiation induces a quicker healing process.…”
Section: Discussionsupporting
confidence: 85%
“…According to the literature, the therapeutical effects of blue light has been reported but its mechanism is still partially unknown, it was observed that blue LED light may be used to modulate the metabolism and proliferation of human fibroblasts, and its effects on wound healing seemed to be particularly evident when studying fibroblast and keratinocyte co‐cultures 26–30 . Other authors considered that it is possible that blue light is absorbed by mitochondrial chromophores in the same way as red/infrared light, but also that can be several other distinct chromophores 31 …”
Section: Discussionmentioning
confidence: 99%
“…Some authors have recently reported observations of an improved healing process when superficial wounds are treated with blue LED light with wavelengths in the range 410–430 nm, and a study in an animal model indicated that blue light led to a faster healing process in superficial lesions, with fibroblasts and myofibroblasts playing an important role [ 19 ]. After a critical literature review [ 22 ], further analyses of this group focused on the effects of blue light on fibroblasts and keratinocytes; it was observed that blue LED light may be used to modulate the metabolism and proliferation of human fibroblasts, and its effects on wound healing seemed to be particularly evident when studying fibroblast and keratinocyte co-cultures [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%